2021
DOI: 10.1371/journal.pone.0246165
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning of EEG spectra classifies unconsciousness during GABAergic anesthesia

Abstract: In current anesthesiology practice, anesthesiologists infer the state of unconsciousness without directly monitoring the brain. Drug- and patient-specific electroencephalographic (EEG) signatures of anesthesia-induced unconsciousness have been identified previously. We applied machine learning approaches to construct classification models for real-time tracking of unconscious state during anesthesia-induced unconsciousness. We used cross-validation to select and train the best performing models using 33,159 2s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Such work has prominently led to the development of the proprietary Bispectral Index Score (BIS), which makes use of several electroencephalographic parameters to estimate DoA, and has been established as the predominant anesthetic monitor used during human surgeries (Dumont, 2012 ). Other published approaches for human DoA estimation rely on non-linear features extracted from electroencephalographic measurements or evoked potentials (Al-Kadi et al, 2013 ), which are used as inputs to traditional machine learning algorithms or artificial neural networks (Li et al, 2020 ; Abel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such work has prominently led to the development of the proprietary Bispectral Index Score (BIS), which makes use of several electroencephalographic parameters to estimate DoA, and has been established as the predominant anesthetic monitor used during human surgeries (Dumont, 2012 ). Other published approaches for human DoA estimation rely on non-linear features extracted from electroencephalographic measurements or evoked potentials (Al-Kadi et al, 2013 ), which are used as inputs to traditional machine learning algorithms or artificial neural networks (Li et al, 2020 ; Abel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, by combining different resting-state or evoked EEG features, previous studies have improved classification between groups or experimental conditions. 38 , 39 , 40 , 41 , 42 , 43 Similarly, previous studies have reported that a combination of EEG features allowed a better characterization of certain brain processes. 44 , 45 , 46 Our results using PCA also show evidence that, for some cognitive variables, latent dimensions of EEG features might be more informative than single features.…”
Section: Discussionmentioning
confidence: 85%
“…To test the filtering methods, there are databases contaminated with motion artifacts [ 266 ]. There are also plenty of publicly available databases for assessment of neurological status in sleep [ 267 ], or in a specific condition, such as anesthesia [ 268 ]. Special attention is also paid to the research of epilepsy, therefore there are also specific databases containing EEG signals during epileptic seizures in both adults [ 269 , 270 ] or pediatric patients [ 271 ].…”
Section: Discussionmentioning
confidence: 99%